Deslocamento e denúncia no romance Sua Majestade, o Juiz, de Jáder de Carvalho - Andrade, Ana Maria Teixeira (2012)
This work explores the romance Sua Majestade, o Juiz (1956) by Jader de Carvalho, whose plot is situated in the historical context of the first half of the 20th century in Ceará. In the book, we studied the space related to the intention of social criticism and denunciation of the author as the structuring agent and organizer of the narrative. In the study, we highlight geographical locations (the capital and cities in the rural parts of Ceará), where the protagonist seeking social mobility moves from one place to another and relates to character representatives of the great power sectors in Ceará such as politicians and judges involved in conservative practices where the clientele base prefers to use public institutions for private purposes. Each new place brings actions and characters to be reported, with an effect of repetition and generalization that reinforces the critical intention of the novel. This happens in the first part of the work, where the focus of the novel is in third person, then in the second part, narrated in first person, with some variations marked throughout the work. To analyze the book from a geographical place, we base our reflections on the theoretical work of Osman Lins about literature (1976), which guide the perception and characterization of areas studied in the work and on the historical-critical studies of Candido (2007b) about the value of geographic space in the Brazilian novel. We use critical thinking of Sérgio Buarque de Holanda (1995) and Roberto Schwarz (2000), which addressed the preference of politicians who maintained public funds for private familial use in Brazilian society. We realized, through the analysis, that the novel raises questions which have a revealing and critical function which is the greatest strength of the book as it is addressed to the opportunistic behavior of the representatives of the governing institutions at that time, who were the greatest promoters of social inequality.